Utilisation Of Islamic Marketing Mix In Resolving Rising Cost Of Living: A Literature Review - Mohammad Tahir Zainuddin (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.